Hexamethylenediamine-Mediated Polydopamine Film Deposition: Inhibition by Resorcinol as a Strategy for Mapping Quinone Targeting Mechanisms - Alfieri, Maria Laura; Panzella, Lucia; Oscurato, Stefano Luigi; Salvatore, Marcella; Avolio, Roberto; Errico, Maria Emanuela; Maddalena, Pasqualino; Napolitano, Alessandra; Ball, Vincent; d'Ischia, Marco (Frontiers in Chemistry, 2019)
Hexamethylenediamine (HMDA) and other long chain aliphatic diamines can induce substrate-independent polymer film deposition from dopamine and several other catechols substrates at relatively low concentrations, however the mechanism of the diamine-promoted effect has remained little understood. Herein, we report data indicating that: (a) film deposition from 1 mM HMDA and dopamine is not affected by chemical oxidation with periodate but is markedly inhibited by resorcinol, which also prevents PDA film formation at 10 mM monomer concentration in the absence of HMDA; (b) N-acetylation of HMDA completely inhibits the effect on PDA film formation; (c) HMDA enables surface functionalization with 1 mM 5,6-dihydroxyindole (DHI) polymerization at pH 9.0 in a resorcinol-inhibitable manner. Structural investigation of the polymers produced from dopamine and DHI in the presence of HMDA using solid state 13C and 15N NMR and MALDI-MS suggested formation of covalent cross linked structures. It is concluded that HMDA enhances polydopamine adhesion by acting both on dopamine quinone and downstream, e.g., via covalent coupling with DHI. These results provide new insights into the mechanisms of PDA adhesion and disclose resorcinol as a new potent tool for targeting/mapping quinone intermediates and for controlling polymer growth.